The Dutch Colonial Policy on Islam: Reading the Intellectual Journey of Snouck Hurgronje - Jajat Burhanudin (Al-Jami'ah Research Centre, 2014)
This article will explore the intellectual journey of Snouck Hurgonje as a hired scholar for the colonial agenda. His life in Mecca and then the Indies, his knowledge on Islam and the Muslims as revealed in the works he produced, and the way it was transformed into the colonial policies, are the main subjects of the discussion. The way Snouck Hurgronje dealt with Muslims on his tour of duty, for example by collaborating with the penghulu, and working together with the Arab, Said Oesman, will also be explored. It should be stated that, in line with Snouck Hurgonje’s advice, the Dutch policy on Islam was directed (among other things) to draw the native elite –in this particular case the penghulu– into the colonial orbit.[Artikel ini membahas perjalanan intelektual Snouck Hurgonje, seorang ilmuwan yang bekerja di bawah dan untuk kepentingan colonial Belanda di Indonesia. Kehidupannya di Mekah, kemudian kembali lagi ke Indonesia, pengetahuannya tentang agama dan orang Islam yang tertuang dalam kerya-karyanya, serta proses pengetahuan itu semua dalam mempengaruhi kebijakan pemerintah kolonial menjadi tema utama diskusi dalam tulisan ini. Selain itu, akan dibahas pula cara-cara Snouck Hurgonje dalam berhubungan dengan orang-orang Islam selama menjalani tugasnya, misalnya ketika bekerjasama dengan para penghulu atau ketika bekerjasama dengan tokoh Arab, Said Oesman. Perlu ditegaskan pula bahwa sejalan dengan saran-saran Snouck Hurgonje, kebijakan pemerintah kolonial Belanda tentang Islam antara lain lebih ditujukan untuk menarik kalangan elit pribumi, dalam hal ini adalah para penghulu, ke lingkaran pemerintah kolonial.]